(untitled) (Journal of Medicine, 2015)
Cardiorenal syndromes (CRS) describe the dynamic inter-relationship between heart and kidney malfunction. Recent studies have clearly defined its various types and pathophysiology. Improved survival, cardiovascular risk factors (diabetes, hypertension, dyslipidemia), diagnostic and therapeutic intervention are some contributors in its causation. Types 1 and 2 CRS involve acute and chronic cardiovascular disease (CVD) scenarios leading to acute kidney injury or accelerated chronic kidney disease. Types 3 and 4 CRS describe acute and chronic kidney disease leading primarily to heart failure, although it is possible that acute coronary syndromes, stroke, and arrhythmias could be CVD outcomes in these forms of CRS. Finally, CRS type 5 describes a simultaneous insult to both heart and kidneys, such as sepsis, where both organs are injured simultaneously. This article focuses on different types, pathophysiology, novel biomarkers, preventive and treatment aspects of cardiorenal syndromes. DOI: http://dx.doi.org/10.3329/jom.v16i1.22400 J MEDICINE 2015; 16 : 39-45